Six new coordination compounds based on rigid 5-(3-carboxy-phenyl)-pyridine-2-carboxylic acid: synthesis, structural variations and properties. Issue 12 (23rd January 2017) - Song, Jiang-Feng; Jia, Ying-Ying; Zhou, Rui-Sha; Li, Si-Zhe; Qiu, Xiao-Min; Liu, Jie
Abstract : Compounds1–6 have rich structural chemistry ranging from mononuclear (1 and2 ), one-dimensional (3 and4 ), two-dimensional (5 ) to three-dimensional (6 ) structures. Abstract : Six new coordination compounds Ni(cppca)(H2 O)4 ·2H2 O (1 ), Co(cppca)(H2 O)4 ·2H2 O (2 ), Cd2 (cppca)2 (H2 O)5 n (3 ), [Cd3 (cppca)2 (H2 P2 O7 )(H2 O)6 ]·2H2 O n (4 ), Cu(Hcppca)2 n (5 ) and [Mn7 (cppca)6 (Hcppca)2 (H2 O)10 ]·2H2 O n (6 ) have been obtained by reactions of the corresponding metal salts and the rigid ligand 5-(3-carboxy-phenyl)-pyridine-2-carboxylic acid (H2 cppca) under solvothermal conditions. All the compounds were fully characterized by single-crystal X-ray diffraction, elemental analysis, IR spectroscopy, thermal analysis and powder X-ray diffraction. The single-crystal X-ray analyses showed that compounds1–6 have rich structural chemistry ranging from mononuclear (1 and2 ), one-dimensional (3 and4 ), two-dimensional (5 ) to three-dimensional (6 ) structures. Moreover, the framework of compound6 may be simplified into a 3-nodal net with Schlafli symbol 4 2 ·64 2 ·8 2 ·10 2 4 3 ·6 2 ·8·10 4 2, which shows an unprecedented (3, 4, 5)-connected topology net. The fluorescent properties of compounds3 and4 were investigated in the solid state and in various solvent emulsions, which indicated that compounds3 and4 are both highly sensitive fluorescent probes for the acetone molecules. Variable-temperature magnetic susceptibility measurements indicate weak antiferromagnetic interactions between metal centers in compounds1, 2, 5 and6 .